Plants, Cities and Communities - Siti Rasidah Md Sakip; Zulkefle Ayob (Penerbit UTHM, 2024)
Plants, Cities and Communities is a must-read chapter for anyone interested in the relationship between plants and the built environment. This book explores plants’ importance and vital roles in our lives and the environment, including their aesthetic value, principles, consumption, application, and benefits to humans facing COVID-19. It also delves into the significant contribution of plants to the health and well-being of the environment and city dwellers. Readers will discover how plants can promote social well-being in urban environments and serve as sustainable materials and sources of traditional knowledge. The book is written in an easy-to-understand language and is accompanied by stunning illustrations and images to create a more exciting and impactful effect. The information in this book chapter is useful, thought-provoking, and suitable for plant enthusiasts, novice designers, and city managers. The objective of the book is to serve as reference material for students and academics in the field of the built environment. It offers invaluable knowledge and a more in-depth perspective into the numerous facets of plants in their natural habitat, urban environment, and their use in academia. With its invaluable knowledge and unique perspective, Plants, Cities and Communities is a book that will undoubtedly be used as a reference source for years to come.